Elementos de estímulo à exportação como alternativa estratégica de negócios: um estudo comparativo nos setores têxtil e de calçados. - Flavio Jose Passos Coelho (2003)
There are numerous factors that can influence the decision-making process of turning a companys business international. In Brazil, many organizations entered the external market because they were motivated by tax incentives and credit facilities offered by the government during the 1970s and 1980s. This historical aspect, along with other culturalaspects, contributed to establishing a certain profile, not always favorable, of the Brazilian exporter. It is at the moment in which the debate regarding the importance of favorable trade balance intensifies, that the discussion about the role of official mechanisms of exportationincentives gains significance. This work, which relies upon data obtained from managers of 62 textile and shoe industries in Minas Gerais, attempts to demonstrate how the exportation incentives are perceived today. For the elaboration of the analysis, comparisons were madebetween different sectors and external factors of exportation incentives, by using the auxiliary tests of Kruskal-Wallis and Friedman, and the Pearsons correlation analysis. A qualitative approach, with the application of deep interviews, served as a means of elaborating theapplied questionnaire as well as highlighting information provided by the quantitative analysis. The results show that managers believe the incentives offered by the government are a crucial aspect for turning Brazilian businesses international. Furthermore, despite theinherent limitations of the study, theoretical and management implications can be drawn by this work.